PERANCANGAN TONGKAT TUNANETRA SENSOR ULTRASONIK MENGGUNAKAN METODE ERGONOMIC FUNCTION DEPLOYMENT (EFD) - Hidayatullah, Muhammad Khanif; Siswiyanti; Tulodo, Rizki Prasetyo (LENVARI, 2025)
The use of a conventional cane for visually impaired individuals still has several limitations, such as discomfort during activities, difficulty aligning the cane with the walking path, and the inability to determine position and destination effectively through tracing or following techniques. Therefore, an improved and more ergonomic cane design is needed. The proposed design incorporates ultrasonic sensors to help users detect obstacles at a greater distance. To ensure user comfort, the design was evaluated using the Ergonomic Function Deployment (EFD) method and supported by anthropometric measurements so that the cane dimensions match user needs. The final design resulted in a cane length of 120 cm, a handle length of 17 cm, and a grip diameter of 3 cm. A paired samples test comparing the conventional cane with the ultrasonic sensor cane showed a sig. (2-tailed) value of 0.000 < 0.05. This indicates that Ho is rejected and Ha is accepted, confirming that the ultrasonic cane provides a significant improvement in usability compared to the conventional cane